Implementation of the Sabhara Patrol in Preventing Illegal Racing Actions at the Labuhan Batu Police - Rizky Trheeyudha Putra (Advances in Police Science Research Journal, 2019)
This research is based on the background of illegal racing in the Labuhanbatu Police area which is one of the traffic problems. The implementation was so organized that the Labuhanbatu Police Sabhara Patrol Unit had difficulty preventing it. This is related to the not yet maximal implementation of the Sabhara Unit patrols in order to prevent illegal racing from occurring. The purpose of this study is to describe the implementation of the Sabhara Unit of the Labuhan Batu Police, the inhibiting factors that affect patrols and how to maximize the implementation of patrols. This study uses concepts and theories that are relevant to the research title, including the concept of implementation, the concept of patrolling, the concept of prevention, the concept of illegal racing, management theory and SWOT theory. This research was conducted using a qualitative approach, using field research methods, as well as data collection techniques with interviews, observations and document studies. This study resulted in research findings, namely, the implementation of the Sabhara Unit of the Labuhan Batu Police in preventing illegal racing at the Labuhan Batu Police, it can be seen from several aspects, namely human resources, administration, budget availability to support the implementation of patrols, implementation time and targets. activity. There are several inhibiting factors that affect the implementation of patrols, both internal and external factors. In addition, efforts to carry out patrols to prevent illegal racing are carried out by maximizing the management function of the Sabhara Unit implemented by the Turjawali Head Office, which is divided into Planning, Organizing, mobilizing, and Controlling. Based on the results of the study, the authors suggest improving the quality and quantity of existing human resources, making patrol routes taking into account the latest security and social security situation, paying attention to the timing of patrols with hours prone to illegal racing, and empowering other agencies to assist the implementation of patrols.